2005
DOI: 10.1007/s00213-005-2155-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute opioid dependence: characterizing the early adaptations underlying drug withdrawal

Abstract: Although not identical phenomena, acute and chronic dependence share a number of characteristics. Examining potentiations of withdrawal severity across multiple acute opioid exposures may be especially valuable in characterizing the development of drug dependence. Further study of acute dependence promises to lead to more effective treatments for opioid withdrawal and addiction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 143 publications
(164 reference statements)
4
48
0
1
Order By: Relevance
“…Increases in the magnitude of the acoustic startle reflex are routinely observed during states of anxiety in rodents, as well as humans (Davis et al, 2010), and anxiety represents one hallmark symptom of drug withdrawal (Koob and Volkow, 2010). There were consistent individual differences between animals in the degree of startle potentiation, and this effect appeared to escalate in severity following repeated drug exposure, consistent with a broader literature showing the severity of withdrawal increases with repeated opiate exposure (Celerier et al, 2001;Harris and Gewirtz, 2005). Increases in the magnitude of withdrawalpotentiated startle were apparent on the Final Test in Experiment 1 following exposure to a moderate dose of morphine (3.2 mg/kg), but were not observed during repeated treatment with 10 mg/kg morphine, which likely reflects an upper limit on the degree of startle potentiation that can be detected during morphine withdrawal.…”
Section: Discussionsupporting
confidence: 74%
“…Increases in the magnitude of the acoustic startle reflex are routinely observed during states of anxiety in rodents, as well as humans (Davis et al, 2010), and anxiety represents one hallmark symptom of drug withdrawal (Koob and Volkow, 2010). There were consistent individual differences between animals in the degree of startle potentiation, and this effect appeared to escalate in severity following repeated drug exposure, consistent with a broader literature showing the severity of withdrawal increases with repeated opiate exposure (Celerier et al, 2001;Harris and Gewirtz, 2005). Increases in the magnitude of withdrawalpotentiated startle were apparent on the Final Test in Experiment 1 following exposure to a moderate dose of morphine (3.2 mg/kg), but were not observed during repeated treatment with 10 mg/kg morphine, which likely reflects an upper limit on the degree of startle potentiation that can be detected during morphine withdrawal.…”
Section: Discussionsupporting
confidence: 74%
“…Responding occurred exclusively on the SAL 3 NTX-appropriate lever when the morphine pretreatment was 24 h. The onset and offset of MOR 3 NTX-appropriate responding occurred with t 1/2 s of 1.68 Ϯ 0.07 and 12.74 Ϯ 1.47 h, respectively. A number of studies have reported signs of spontaneous withdrawal after acutely administered morphine (for review, see Harris and Gewirtz, 2005), including subjective signs in humans (Kirby and Stitzer, 1993). Morphine followed 16 h later by saline resulted only in responding on the SAL 3 NTXappropriate lever (Fig.…”
Section: Downloaded Frommentioning
confidence: 99%
“…The phenomenon of acute dependence is predominantly mediated via -opioid receptors and is stereoselective (Ramabadran, 1983;Adams and Holtzman, 1990; Holtzman, 1997, 1999;White and Holtzman, 2003). The severity of withdrawal from acute opioid dependence is critically dependent upon the doses of agonist and antagonist used as well as the interval between agonist and antagonist administration (Harris and Gewirtz, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations